Gadolinium‐Conjugated Gold Nanoshells for Multimodal Diagnostic Imaging and Photothermal Cancer Therapy. Issue 3 (23rd September 2013) - Coughlin, Andrew J.; Ananta, Jeyarama S.; Deng, Nanfu; Larina, Irina V.; Decuzzi, Paolo; West, Jennifer L.
<x xml:space="preserve">Abstract</x> Multimodal imaging offers the potential to improve diagnosis and enhance the specificity of photothermal cancer therapy. Toward this goal, gadolinium‐conjugated gold nanoshells are engineered and it is demonstrated that they enhance contrast for magnetic resonance imaging, X‐ray, optical coherence tomography, reflectance confocal microscopy, and two‐photon luminescence. Additionally, these particles effectively convert near‐infrared light to heat, which can be used to ablate cancer cells. Ultimately, these studies demonstrate the potential of gadolinium‐nanoshells for image‐guided photothermal ablation.